2011
DOI: 10.1103/physrevb.83.195320
|View full text |Cite
|
Sign up to set email alerts
|

Exciton pattern generation in GaAs/AlxGa1xAs multiple quantum wells

Abstract: Exciton pattern generation inGaAs/AlxGa1−xAs multiple quantum wells Phys. Rev. B 83, 195320 (2011) http://hdl.handle.net/10945/51345 Downloaded from NPS Archive: Calhoun PHYSICAL REVIEW B 83, 195320 (2011) Exciton pattern generation in GaAs/Al x Ga 1−x As multiple quantum wells Exciton photoluminescence pattern generation is investigated in multiple quantum wells. High-contrast outer rings and localized bright spots are generated using efficient field-assisted upconversion of laser light whose photon ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In those works, the inhomogeneities in the condensate density were caused by the interactions of polaritons with a cloud of non-condensed excitons and with structural defects in the cavity. The ring pattern formation was earlier demonstrated for the dipolar excitons in coupled QWs and multiple QWs in previous experimental and theoretical works [3,24,58,68,69]. In spatially resolved measurements, the photoluminescence of the dipolar exciton pattern was seen as a central laser excitation spot surrounded by a sharp ring-shaped region with a diameter much larger than that for the spot and with large dark regions separating the two.…”
supporting
confidence: 55%
“…In those works, the inhomogeneities in the condensate density were caused by the interactions of polaritons with a cloud of non-condensed excitons and with structural defects in the cavity. The ring pattern formation was earlier demonstrated for the dipolar excitons in coupled QWs and multiple QWs in previous experimental and theoretical works [3,24,58,68,69]. In spatially resolved measurements, the photoluminescence of the dipolar exciton pattern was seen as a central laser excitation spot surrounded by a sharp ring-shaped region with a diameter much larger than that for the spot and with large dark regions separating the two.…”
supporting
confidence: 55%
“…In addition, a narrow (inner) luminescence ring is formed around the excitation spot itself [6,[8][9][10]. On the one hand, it has been established that the outer-ring signals the recombination between optically and electrically injected carriers [11,12]. On the other hand, the origin of the inner photoluminescence ring has first been attributed to a laser induced heating of indirect excitons: combined experimental and theoretical studies have shown that the inner luminescence ring is the signature of the transport and subsequent cooling of the indirect excitons outside the excitation spot [8,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, more convincing evidences for observing the excitonic BEC in semiconductors are still desirable. Recently, the indirect excitons between two coupled quantum wells demonstrated a long-range coherent transport with a distance from a few hundreds of micrometers up to 1 mm [7,[11][12][13][14][15]. However, the mechanism for this long-distance coherent transport is still under debate, although several mechanisms have been proposed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%